Hydrological connectivity shape the nitrogen pollution sources and microbial community structure in a river-lake connected system - Chen, Haoda; Zhang, Lulu; Zheng, Zishuai; Gao, Yuang; Zhao, Yu (Frontiers in Microbiology, 2025)
Intensified agricultural and urban activities have exacerbated nitrogen pollution, posing a severe threat to freshwater ecosystems, particularly under intensified agricultural and urbanization activities. This study systematically examined Baiyangdian Lake (BYD) and its principal inflowing rivers, namely Fu River (FH), Baigouyin River (BGY), and Xiaoyi River (XY) to characterize the spatio-temporal distribution, primary nitrogen sources, and the impact on sediment microbial community structure. Results indicated pronounced seasonal variations in both nitrogen pollution loads and sources, with riverine nitrogen levels rising markedly from dry season (May) to wet season (August). Atmospheric deposition accounted for 43.9% of the nitrogen input dry season, whereas in wet season, agricultural fertilizers and sewage contributed 23.3 and 26.4%, respectively. Additionally, microbial communities exhibited distinct temporal and spatial patterns, with significantly higher diversity and species richness being during the wet season. The, microbial composition shifted, as evidenced by a decline in Proteobacteria and increases in Firmicutes and Actinobacteriota. River-lake connectivity emerged as a critical factor, with FH displaying a notably higher connectivity index in wet season compared to BGY and XY rivers. Structural equation modeling (SEM) analysis further revealed that river-lake connectivity was significantly and positively correlated with nitrogen pollution, was significantly and negatively correlated with microbial α-diversity. These findings demonstrated that river-lake connectivity directly influenced nitrogen concentrations, which in turn indirectly modulated microbial diversity.